INOVASI KURIKULUM BAHASA ARAB MADRASAH ALIYAH BERBASIS KONTRUKTIVISME - Prabowo Adi Widayat (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
The curriculum used in each educational institution is a guideline that contains a description in general terms about the fine points of the learning material that must be implemented by educational institutions through teachers and students in an atmosphere of learning. The Arabic language as a compulsory subject in the madrasah aliyah should have a curriculum to suit the needs and challenges of the times. Arabic language curriculum must emphasize the importance of communicative and scientific approach in learning, because both approaches can accommodate the language learners practice and theoretically. Constructivism become part of current curriculum innovation. This theory emphasizes the importance of building knowledge gained with the sturdy cognition through communicative and interactive learning experiences between teachers and students in the school environment. In the Arabic language curriculum innovation, this theory gives the principles should be implemented including the following; physical learning material knowledge, knowledge of mathematical logic that are structural or based on norms of knowledge is studied, and the social sciences that emphasized the importance of communicative interaction in diverse environments.